An Analysis of the Driving Factors Behind Afghan Youth Migration to Türkiye - Shafaq, Abdul Qayum; Shuaa, Hameedullah (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This study investigates the factors driving Afghan youth migration to Turkey using primary data from 199 respondents via an online survey. Analysis of demographic characteristics and migration experiences reveals that Afghan youth migrants to Turkey, predominantly male (73.9%) with an average age of 28 years, hold high levels of education, with 43.2% possessing bachelor’s degrees and 32.7% holding master’s degrees. The research finds that a significant portion of Afghan youth migrants encounter challenges and discrimination during migration, with 80.4% reporting difficulties and 68.8% experiencing discrimination. Furthermore, a large majority (84.4%) do not intend to remain in Turkey, indicating a transient migration pattern. Key push factors identified include political instability (cited by 57.8% of respondents) and economic factors such as unemployment and poverty (influencing 34.7% of respondents). Conversely, the education system in Turkey emerges as a prominent pull factor, influencing migration decisions for 49.2% of respondents. Correlation analysis shows a statistically significant positive relationship (Pearson correlation coefficient = 0.187**, p = 0.008) between satisfaction with migration and pull factors, emphasizing their importance. Regression analysis highlights the impact of political factors, support from the Turkish government, and integration into Turkish society on satisfaction with migration decisions. Notably, political factors (B = 0.134, p = 0.042), government support (B = 0.173, p = 0.004), and integration (B = 0.204, p = 0.011) significantly influence satisfaction. Findings offer insights for cross-cultural workforce integration management, providing valuable implications for policymakers and organizations working with migrant populations.